Audit Switching, Tenure, Fees, and Audit Report Lag in Indonesian Property Firms - Vimas Wilanda; Damayanti Damayanti; Evi Yuniarti (Jurnal Bisnis dan Pemasaran Digital, 2026)
Purpose: This study examines whether auditor switching, audit tenure, and audit fees are associated with audit report lag in Indonesian property and real-estate firms.Research Methodology: The research employs a quantitative archival design, analyzing a balanced sample of 27 listed property firms from 2021 to 2024 (108 firm-years) using robust regression and fixed-effects models.Results: The average audit report lag in the sample is 91.06 days. Auditor switching, tenure, logged audit fees, and firm size do not show statistically significant individual associations with audit report lag in both specifications.Conclusions: The reconstructed data do not provide reliable evidence that the three focal audit attributes are individually associated with audit report lag.Limitations: The analysis uses rounded appendix tabulations because the underlying annual reports and raw analysis file were unavailable.Contributions: Theoretically, this study clarifies how panel sensitivity analysis and sample retention shape the interpretation of non-causal evidence in sector-specific research. Practically, it alerts audit committees that auditor changes, tenure, or fees are not standalone predictors of reporting delay, while establishing strict data-traceability requirements for future timeliness studies.